First time in forever - Morgan, Sarah, 1948- (Morgan, Sarah, 1948- Puffin Island novel., 2015)
Emily Donovan has moved to Puffin Island to be a stand-in mother for her niece Lizzy. Between desperately safeguarding Lizzy and her overwhelming fear of the ocean, Emily has lost count of the "just breathe" pep talks she has given herself. And that's before charismatic local yacht club owner Ryan Cooper kisses her. Ryan knows all about secrets and it's clear to him that Emily is hiding something. So Ryan decides he's going to help her unwind and enjoy the sparks between them. But can Puffin Island work its magic on Emily and get her to take the biggest risk of all: putting her heart in someone else's hands?